Pengembangan Media Digital untuk Meningkatkan Literasi Ekonomi Siswa - Wandira, Nur Rahayu; Hardaningrum, Tri Wahyu (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The abstract version of the English is written using the English version of the British in past tense and appropriate sentences. The result and conclusions are written in the form of the present tense. Abstracts are expected to be more communicative and not monotonous. A simple sentence is English contains a minimum of subject and predicate elements. Economic literacy is the ability to use basic economic concepts and critical thinking in making decisions (Solihat & Arnasik, 2018). Therefore, economic literacy is one of the skills that must be possessed because economic literacy is a useful tool for changing behavior from unintelligent to intelligent. Like how to save, invest, protect and make ends meet (Sina Garlans, 2012). In the development of the ability to economics also continues to grow. One of them is the emergence of digitalization in economic activities. So it is important to have economic literacy needed in the modern era of the 21st century (Anggreini & Waspada, 2020), namely digital economic literacy, especially for high school students who are among the highest internet users in Indonesia. Because it is hoped that they can take a positive impact from the existence of the digital economy, and avoid digital crime. Therefore researchers conduct research and development using the Borg and gall procedural model, to produce products, namely digital media which are learning media that apply the use of technology, information, and communication to convey information (Jannah Noer Rahmawati & Atmojo Widianto Ragil, 2022), by loading digital economic material to increase students' economic literacy. The results showed that digital media is feasible to use in the very valid category with a combined validation result of 87.5%, consisting of 97% from media experts, 81% from material experts, and 86% from audiance validation. As well as being able to increase students' economic literacy with an n-gain test result of 0.68 which is in the moderate or quite effective category